2022
DOI: 10.5194/angeo-2022-17
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of the terdiurnal tide on the Sporadic-E layers (Es) development at low latitudes over the Brazilian sector

Abstract: Abstract. Sporadic-E (Es) layers are patches of high ionization observed at around 100–140 km height in the E region. Their formation at low latitudes are primarily associated with the diurnal and semidiurnal components of the tidal winds via the ion convergence driven by the wind shear mechanism. However, recent studies have shown the influence of other tidal modes, such as the terdiurnal tide. Therefore, this work investigates the effect of terdiurnal tide-like oscillations on the occurrence/formation of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Fontes et al. (2023) investigated the terdiurnal tide‐like oscillations on the Es occurrences over Palmas and found a modulation of 8‐hr in all seasons of the year. However, the authors noted that this effect was observed to be at a minimum during December.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Fontes et al. (2023) investigated the terdiurnal tide‐like oscillations on the Es occurrences over Palmas and found a modulation of 8‐hr in all seasons of the year. However, the authors noted that this effect was observed to be at a minimum during December.…”
Section: Results and Analysismentioning
confidence: 99%
“…This classification is based on the observation that during nighttime the ftEs/fbEs parameters tend to be generally lower than during daytime (see Figure 1), primarily due to reduced ionization levels. As both Es f and Es l types present similar signatures in the ionograms, some studies (Conceição‐Santos et al., 2019; Fontes et al., 2023) group them into a single type (Es f/l ). It is noteworthy that both “f” and “l” types persist throughout the day, which indicates that they may be formed by metallic ions that have longer lifetimes compared to molecular ions (Plane et al., 2015).…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation